2019
DOI: 10.1177/1057567719896020
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting Disorder Perceptions: Neighborhood Structure and the Moderating Role of Interethnic Contact and Xenophobic Attitudes

Abstract: Although urban disorder has played a central role in neighborhood research, its impact may have been overstated in studies relying on the subjective perception of survey respondents only. Research on the “perception bias”—defined as the divergence between respondents’ subjective assessments and systematic observations of disorder—has revealed the ambiguous nature of disorder and opened a door to the analysis of the social construction of this environmental cognition. Using survey and observational data from 14… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 116 publications
2
11
0
1
Order By: Relevance
“…Moreover, there was little theoretical motivation to aggregate to some area-level that could be subject to additional sources of error such as the modifiable areal unit problem [ 59 ]. Studies that have performed aggregations have noted the high correlations between objective neighborhood disorder values within areas, similar to the spatial autocorrelation partial sill and range that we report [ 6 , 51 , 52 ]. Our methodology aligns with other studies involving observed and perceived neighborhood factors [ 13 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Moreover, there was little theoretical motivation to aggregate to some area-level that could be subject to additional sources of error such as the modifiable areal unit problem [ 59 ]. Studies that have performed aggregations have noted the high correlations between objective neighborhood disorder values within areas, similar to the spatial autocorrelation partial sill and range that we report [ 6 , 51 , 52 ]. Our methodology aligns with other studies involving observed and perceived neighborhood factors [ 13 , 60 ].…”
Section: Discussionsupporting
confidence: 83%
“…Though this is the first known path analysis of these neighborhood and socioeconomic variables among Black breast cancer survivors, related studies have yielded similar findings. Early studies of perceived neighborhood disorder by Sampson and Raudenbush (2004) and Franzini et al (2008) observed similar associations involving audited neighborhood disorder, individual socioeconomic status, and neighborhood social ties/exchanges (i.e., a construct related to social cohesion), which more recent studies have generally confirmed [ 51 53 ]. These previous studies also found mixed associations involving area-level African American/Black composition.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Individual scores were derived from a Confirmatory Factor Analysis model using perceptions of how much of a problem noisy neighbours, teenagers hanging around, rubbish or litter, vandalism or graffiti, being attacked because of skin colour, drug dealing, people being drunk or rowdy, abandoned or burnt out cars, and people being harassed or intimidated are in the local area (CFI = 0.947, TLI = 0.930, RMSEA = 0.082). Previous studies have demonstrated the crucial role of a 'perception bias' that filters individual assessments of disorder via personal characteristics (Janssen et al, 2019), however at broad spatial scales like Local Authorities it may be a proxy measure for more objective signs of disorder.…”
Section: Rcme: Worked Examplesmentioning
confidence: 99%
“…Erst in jüngerer Zeit nehmen empirische Studien aus Deutschland das Thema in Angriff und gelangen dabei zu unterschiedlichen Ergebnissen. Befunden, wonach Personen mit Zuwanderungsbiographie häufiger von Kriminalitätsangst betroffen sind als die einheimische Bevölkerung(Birkel et al 2019;Oberwittler & Zirnig 2016), stehen Hinweise auf eine in Migrantenkreisen geringere kriminalitätsassoziierte Verunsicherung gegenüber(Janssen et al 2019;Oberwittler et al 2017).…”
unclassified